Magnetic domains in spinor Bose–Einstein condensates - Matuszewski, Michał; Alexander, Tristram J.; Kivshar, Yuri S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
We discuss the structure of spin-1 Bose–Einstein condensates in the presence of a homogenous magnetic field. We demonstrate that the phase separation can occur in the ground state of antiferromagnetic (polar) condensates, while the spin components of the ferromagnetic condensates are always miscible, and no phase separation occurs. Our analysis predicts that this phenomenon takes place when the energy of the lowest homogenous state is a concave function of the magnetization. We propose a method for generation of spin domains by adiabatic switching of the magnetic field. We also discuss the phenomena of dynamical instability and spin domain formation.